The annual life history of a population of Derallus angustus Sharp (Coleoptera, Hydrophilidae) - Fernandez, Liliana Alicia (2008)
Derallus Sharp, 1882 is a Neotropical genus of aquatic coleopterans that belongs in the tribe Berosini and includes 15 species. D. angustus Sharp is widely distributed from Guatemala to Argentina. The population dynamics of this species was studied by periodic sampling of a natural population from the southernmost Subtropical Domain of the Neotropical Region. The study site was near Punta Lara (34 degrees 47' S, 58 degrees 01' W; Ensenada, Buenos Aires province, Argentina). Twenty seven samples consisting of 20 units of aquatic vegetation (200 cm2 each) were taken during one year. Larvae and adults were removed from the vegetation and counted (pupae were not studied). There was a peak of first instar larvae abundance at the end of spring, and another at the end of summer. Adults and third instar larvae were present throughout the whole year. The population is interpreted as being univoltine and including two periods of enhanced reproductive activity.